Gender, Citizenship and Newspapers - Chapman, Jane L. author. aut Link
XVI, 238 p.
Keywords: The gendered nature of the relationship between the press and emergence of cultural citizenship from the 1860s to the 1930s is explored through original data and insightful comparisons between India, Britain and France in this integrated approach to women's representation in newspapers, their role as news sources and their professional activity.